Association of sleep apnoea risk and aortic enlargement in Marfan syndrome - Harry Dietz; Mudiaga Sowho; Gretchen MacCarrick; Jonathan Jun; Alan R Schwartz; Enid R Neptune (BMJ Open Respiratory Research)
Background Marfan syndrome (MFS) is a connective tissue disorder characterised by complex aortic pathology and a high prevalence of obstructive sleep apnoea (OSA). OSA produces intrathoracic transmural stresses that may accelerate aortic injury. The current study was designed to examine the associations between OSA risk and markers of aortic enlargement in MFS.Method Consecutive patients with MFS were recruited at Johns Hopkins if they completed a STOP-BANG survey. Composite survey scores were categorised into those with low OSA risk (STOP-BANG <3) and high OSA risk (STOP-BANG ≥3). Participants’ aortic data were collated to ascertain aortic root diameter, dilatation and prior aortic root replacement. Regression analyses were used to examine associations between OSA risk strata and these aortic parameters.Results Of the 89 participants studied, 28% had a high OSA risk and 32% had aortic grafts. Persons with high OSA risk had greater aortic root diameter (mm) (ß=4.13, SE=1.81, p=0.027) and aortic root dilatation (ß=2.80, SE=1.34, p=0.046) compared with those with low OSA risk . In addition, the odds of prior aortic root replacement was three times greater in those with high OSA risk compared with those with low OSA risk.Conclusion In MFS, high OSA risk is associated with aortic enlargement and a threefold increased risk of having had prior aortic root replacement. These findings invite further exploration of the relationship between OSA and aortic disease in MFS, and studies to clarify whether targeted interventions for OSA might mitigate aortic disease progression in MFS.Registration number IRB00157483.